Real options and investment under uncertainty : (MIT Press, 2001)
The study of investment under uncertainty was stagnant for several decades, until recent developments in real options provided the tools to revitalize the field. The techniques and insights derived from option pricing can now be used to quantify the elusive elements of managerial operating flexibility and strategic interactions ignored or underestimated by conventional Net Present Value and other quantitative approaches. Topics covered include the reasons for the under-investment problem and conceptual frameworks for viewing productive investment opportunities as real options; useful valuation building blocks; the quantifying of various types of real options separately and in combination; strategic aspects of investment under uncertainty; numerical analysis techniques; a variety of applications, including the valuing of natural resources, R&D and pioneer ventures, land development, strategic acquisitions, government subsidies, power plants and pollution options, flexible manufacturing, and multinational operations; and empirical evidence from oil leasing, land prices, and discontinued operations.